Preparation of geopolymer for in-situ pavement construction on the moon utilizing minimal additives and human urine in lunar regolith simulant - Chen, Lichong; Wang, Tao; Li, Feng; Zhou, Siqi (Frontiers in Materials, 2024)
Constructing lunar pavements is of great significance for improving the transportation efficiency of materials and personnel transfer at lunar bases. Utilizing lunar regolith for the in-situ preparation of geopolymer is an effective means of supplying raw materials for lunar pavement construction. This present study prepared geopolymers for pavement material with lunar regolith simulant. The influence of NaOH on the compressive strength of geopolymers was understood by using different percentages of NaOH as alkaline activator. The effect of urine on the compressive strength of geopolymers by using artificial urine of different pH values as liquid phases. The results indicated that the addition of artificial urine slightly reduces the compressive strength of geopolymers, and the effects of pH and NaOH percentage are different. Microstructural analysis performed by Mercury Intrusion Porosimetry and Scanning Electron Microscope, indicated that choosing fine-particle lunar regolith simulant as precursor is more conducive to the preparation of high-strength geopolymers using human urine.